Hubungan Peran Orang Tua Sebagai Model Dengan Perilaku Disiplin Mahasiswa Jurusan Pastoral Konseling STAKN Kupang - Rini Meitri Tube; Delsylia Tresnawaty Ufi (SOLIDARITY: Journal of Social Studies, 2021)
ABSTRACT The role model of parents is inportant in shaping disciplinary behavior through mentoring, communication, giving trust, supervision, motivation and directing self-discipline. This study is to determine whether there is a relationship between the role of parents as a model and disciplinary behavior of students majoring in Pastoral Counseling STAKN Kupang. This research is a population study with a total of 67 students of the Department of Pastoral Counseling Semester IV STAKN Kupang. Product-moment correlation was used to analyze data. The result is the relationship between the roles of parents as a model with the disciplinary behavior of students of the Department of Pastoral Counseling Semester IV STAKN Kupang amounting to 41.9% with the